Steroid hormone interconversions in human adipose tissue in vivo. - Boulton, K; Hudson, D; Coppack, S; Frayn, K (1992)
The objective of this study was to demonstrate directly, by measurement of arteriovenous concentration differences, the interconversion of steroid hormones in human subcutaneous adipose tissue in vivo. Simultaneous arterial (or arterialized) and adipose tissue-venous plasma samples were collected from eight men and seven women, for measurement of estradiol, estrone, testosterone, and androstenedione concentrations by radioimmunoassay. Despite the heterogeneity of the groups (premenopausal and postmenopausal women, one subject with insulin-dependent diabetes mellitus), some very consistent findings emerged. Both estrogens were added to plasma during passage through adipose tissue in almost all subjects (P less than .01 for each hormone). In all the men but one, testosterone was removed from plasma, and the arteriovenous difference was correlated with the arterial concentration (r = .70, P = .05). In all the women but one (in whom there was no change), the testosterone concentration increased during passage through adipose tissue. The handling of androstenedione was less consistent. This study demonstrates the feasibility of direct measurement of the peripheral production or utilization of steroid hormones, and confirms the belief that adipose tissue is an important site for such interconversions.